FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2014) - Rijal Pasya Ramdani (AKT 16 UMY 176, 2016)
This study aimed to analyze Factors Affecting the Profitability of Companies. The object of this research is a manufacturing companies consumer goods industry sector listed in Indonesia Stock Exchange Year 2012-2014. In this study sample was 66 used samples selected by purposive sampling method. Analysis tool used is the Statistical Product and Service Solutions (SPSS. 15) Based on the analysis that has been done shows that the turnover of accounts receivable and inventory turnover significantly affect profitability, but variable cash turnover did not affect the profitability. Keywords: Cash Turnover, Accounts Receivable Turnover, Inventory Turnover and Profitabilit